Study on Preparation Process and Electrical Properties of Diamond PN Junction - Liu, Yufei (Transactions on Computer Science and Intelligent Systems Research, 2024)
Diamond PN junctions exhibit exceptional properties such as high electric breakdown field, the largest bandgap and the highest thermal conductivity compared to any known materials. These unique attributes make diamond highly suitable for high-power, high-frequency and harsh-environment applications. Currently, chemical vapor deposition (CVD) and high-pressure high-temperature (HPHT) methods can be used to synthesize diamond substrates. Among these, synthetic diamond produced by CVD has garnered significant interest due to its distinctive combination of exceptional electrical and thermal properties. However, its extremely high mechanical hardness and smaller substrate size pose substantial challenges for the implementation of device technology. This paper aims to explore the distinguished properties of diamond in electronics and the preparation process of diamond PN junctions, focusing on synthesis technologies, doping issues and terminal technologies. All of these are critical for maximizing the dependability and performance of electronic devices based on diamonds. By addressing these challenges, the research seeks to forward the application of diamond in various high-performance electronic devices, highlighting its capacity to improve device durability and effieciency in harsh operating conditions. The insights provided will contribute to a deeper understanding of the material’s capabilities and the technological advancements necessary to harness its full potential in electronic applications.